2019
DOI: 10.1634/theoncologist.2019-0365
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Use of Archived Biospecimens from Oncology Trials When Adequacy of Informed Consent Is Unclear

Abstract: Background Oncology research increasingly involves biospecimen collection and data sharing. Ethical challenges emerge when researchers seek to use archived biospecimens for purposes that were not well defined in the original informed consent document (ICD). We sought to inform ongoing policy debates by assessing patient views on these issues. Materials and Methods We administered a cross‐sectional self‐administered survey to patients with cancer at an academic medical center. Survey questions addressed attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…For example, Jeffrey Peppercorn and colleagues recently found that 65 percent of cancer patients in their study approved of the sharing of their leftover specimens after surgery, even without their consent. 36 Similarly, Michelle Mello et al found that 93 percent of respondents in their study, all of whom participated in clinical trials, were very or moderately willing to share both biospecimens and other health data as part of clinical trials. 37 Respondents also thought the possibility of being reidentified based on their information was very low, with few saying that identification (6.6 percent) or discrimination based on identification (5 percent) was among their biggest concerns.…”
Section: Communicating Genomic Identification Risksmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, Jeffrey Peppercorn and colleagues recently found that 65 percent of cancer patients in their study approved of the sharing of their leftover specimens after surgery, even without their consent. 36 Similarly, Michelle Mello et al found that 93 percent of respondents in their study, all of whom participated in clinical trials, were very or moderately willing to share both biospecimens and other health data as part of clinical trials. 37 Respondents also thought the possibility of being reidentified based on their information was very low, with few saying that identification (6.6 percent) or discrimination based on identification (5 percent) was among their biggest concerns.…”
Section: Communicating Genomic Identification Risksmentioning
confidence: 87%
“…Support is especially strong among those who are familiar with sharing health data. For example, Jeffrey Peppercorn and colleagues recently found that 65 percent of cancer patients in their study approved of the sharing of their leftover specimens after surgery, even without their consent 36 …”
Section: Communicating Genomic Identification Risksmentioning
confidence: 99%
“…First, as appropriate for an exploratory qualitative design, the sample was small and drawn from a single precision oncology sequencing study of one disease site and might not be representative of patients with cancer generally. In addition, patients with cancer comprise a special population and might be more willing to contribute sensitive genetic data to research, given the serious nature of their disease, than other patients [22,23]. Also, we originally designed our interview instrument to assess participant feelings regarding profit investment rather than informed consent form comprehension; an explicit question or knowledge test about the consent form may have revealed such misunderstandings to be more widespread.…”
Section: Discussionmentioning
confidence: 99%
“…• Who: identity of data overseers [11,31,41,49,53,76,83,85,98,[100][101][102]115] and data users [11,31,33,34,36, about biobanking generally centered around the control and ownership of biological [11,31,52,[73][74][75][76][77][79][80][81]86,91,113,114,[40][41][42]49,[52][53][54]57,59,60, samples and data, especially with respect to potential misuse by insurers, the government and other third parties" (Joly et al [64] on the views of members of the public). 117,118] • "I'm just trying to say there is this framework, you know we say that there is a governance system in place which will protect the patient and we can look at them…”
Section: Information On Data Governancementioning
confidence: 99%